2016
DOI: 10.1093/geronb/gbw050
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attitude Toward Own Aging for Fluid and Crystallized Functioning: 12-Year Evidence From the ILSE Study

Abstract: This study adds to the understanding of long-term implications of aging attitudes for cognitive decline trajectories and shows that negative aging attitudes are a risk factor for age-vulnerable cognitive abilities, particularly among men. Further research is needed to better understand the underlying mechanisms of observed relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 34 publications
4
49
1
Order By: Relevance
“…For instance, people who report a younger SA generally indicate better psychological well-being, health and cognitive functioning and even lower mortality (for recent examples, see Kotter-Grühn et al 2009 ; Stephan et al 2011 , 2013 ). Similarly, several studies have demonstrated that scores on the ATOA predict physical and cognitive functioning or mortality over and above, for example, self-efficacy, self-rated health (Siebert et al 2018 ; Tovel et al 2019 ) or hope (Levy et al 2002 ). Scores on the AgeCog scales have been found to be longitudinally related to health over and above control beliefs (Wurm et al 2007 ) and to physical exercise (Wurm et al 2010 ).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, people who report a younger SA generally indicate better psychological well-being, health and cognitive functioning and even lower mortality (for recent examples, see Kotter-Grühn et al 2009 ; Stephan et al 2011 , 2013 ). Similarly, several studies have demonstrated that scores on the ATOA predict physical and cognitive functioning or mortality over and above, for example, self-efficacy, self-rated health (Siebert et al 2018 ; Tovel et al 2019 ) or hope (Levy et al 2002 ). Scores on the AgeCog scales have been found to be longitudinally related to health over and above control beliefs (Wurm et al 2007 ) and to physical exercise (Wurm et al 2010 ).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, while previous findings indicated that subjective age may be associated with changes in general health, cognitive functioning (Demakakos et al , 2007; Stephan et al , 2011) and wellbeing (Keyes and Westerhof, 2012), and may be also affected by daily events (Kotter-Grühn et al , 2015), the list of reasons to feel old included in the survey was limited to a few of these conditions. Furthermore, constructs such as attitudes towards own ageing, awareness of age-related change and subjective nearness/distance to death may mediate subjective perceptions of ageing (Brothers et al , 2017; Siebert et al , 2018). Therefore, it is possible that they also play a role in attributing significance to the specific experiences people associate with their ageing process.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were controlled for sociodemographic variables, i.e. gender (male = 1, female = 2), education (number of years at school and university), and–given that health and cognition are both meaningfully related to personality [51, 52] and ATOA (e.g., [12, 10])–also for baseline objective and subjective health status and cognitive abilities at T1. We restricted the inclusion of covariates to those variables assessed at T1 due to reasons of parsimony and the inconsistent measurement of covariates at different assessment waves.…”
Section: Methodsmentioning
confidence: 99%